Problems and Insights on Space: The Effects of Phenomenology Theory on the Concept of Space - Ulubay, Serhat; Onal, Feride (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
This study was an examination of a change in the means and manner of comprehension of the concept of space and the questions it stimulated as a result of the emergence and development of phenomenology theory in the last century. Phenomenology theory is based on the argument that our understanding of phenomena is related to our consciousness and promotes a different and deeper form of comprehension by asking questions about the essence of existence. The movement grew in the early 20th century, and challenged the dominant view of rational reality and Cartesian assumptions. Phenomenology encourages questioning what has been defined as concrete and immutable, arguing that phenomena can be grasped through internal experience rather than simply visible physical appearance and predefined ideas. According to this new concept, all of our acquisitions we call experience help us make sense of phenomena. Science makes its inquiries based on adopted and accepted experiences about the world. However, the phenomenological approach suggests that all adopted data, including the fundamentals of science, should also be questioned. The essential objective of the phenomenological philosophy is the extension of the field of questioning to explore the essence of facts and primary phenomena. This radical questioning deeply affected and altered the intellectual agenda of the time. Philosophers discussed and examined the intrinic meaning of many phenomena. The concept of space lends itself to this new kind of assessment. Phenomenology theory, which aims to contribute to the base of scientific knowledge and to increase the critical foundations of philosophy, opened the prevailing semantics of space perceived as an object defined with rational boundaries and mathematical assumptions to discussion. Phenomenological opinion, contrary to the Cartesian way of thinking, argues that space cannot be deliniated by the patterns of a single reality and that an infinite number of descriptors that we discover through our acts and experiences can be applied. This vision of space is discovered through all of our direct life experiences and queries of all realms, including the social and cultural arenas, psychology and the human body, ideas of the self and the question of existence, as well as hard science. Different methodologies applied by philosophers of the phenomenology school of thought diversified the basis of questioning and definition, and thereby enriched the concept of space. This study examines the methods of reading and questioning the definition of space used by phenomenological theorists and the contributions this interpretation brought to the conceptualization of space. The critical approach of the Cartesian way of thinking was compared and contrasted with the phenomenological view. All of the acquisitions and dynamics of life are in a state of constant change. The structure of societies, the way they comprehend the world, cultural and individual mental acts are not fixed like a photograph pausing a moment. A Cartesian view considers space to be a static and frozen object. A primary contribution of phenomenology to the intellectual environment of the last century was to encourage exploration of the fact that the mode of questioning has no boundaries, that the accepted realities cannot constitute the only starting point of our questioning. In addition, it reminded us that all our social and individual experiences are a means to grasp and comprehend the concept of space. We exist in this world through our thoughts, perceptions, memory, and body; therefore, we can comprehend phenomena, including space, via all of our life experience. This study examined how the idea of space has been shaped over time, focusing on the principles of phenomenological questioning and sixteen theorists considered pioneers of this way of thinking. The questioning put forward by phenomenology changes kinetically, and it is possible that such theories of the evaluation of space can be a tool for the diversification of today's thought on the subject and the discovery of news ideas of space.
Keywords: Cartesian philosophy; consciousness acquisitions; perception; phenomenology; space; Architecture